(untitled) (LIS TODAY, 2021)
This Paper is prepared to make aware the Person with Visual impairment as well as Librarians who is serving to visually impaired community about assistive technology. It dwells upon the use and importance of assistive technologies in general and their use for visually Impaired Library users in particular. Further, it gives suggestions for implementing assistive technologies in Public libraries for making visually Impaired Library users and self-reliant learners in accomplishing their academic and research pursuits.